Gender Differences in Pulmonary Function, Respiratory Symptoms, and Macrophage Proteomics among HIV-Infected Smokers - Shiva D. Rahmanian; Karen L. Wood; Shili Lin; Mark A. King; April Horne; Shangbin Yang; Haifeng M. Wu; Philip T. Diaz (Scientifica)
Background. HIV-infected subjects have an increased incidence of pulmonary emphysema. There are known gender differences in COPD phenotypic expression and diagnosis, but this is not well characterized in lung disease related to HIV. We analyzed a group at risk for the development of COPD (HIV-infected smokers) to determine gender differences in pulmonary symptoms, pulmonary function tests, and HRCT appearances. Methods. This was a cross-sectional, baseline analysis of a prospective study performed between 2006 and 2010. We performed symptomatic, pulmonary function, and computed tomography assessments in 243 HIV-infected smokers. In a subset bronchoalveolar lavage was performed with proteomic analysis of their alveolar macrophages. Results. The majority of the participants were male 213 (87.6%). There was significantly higher percentage of cough and phlegm production in males. There was also a lower FEV1 and a higher RV in males than females. Proteomic analysis revealed 29 proteins with at least a 2-fold higher expression in males and 13 identified proteins that were higher in females. Conclusions. In this group of HIV-infected smokers, airway symptoms and pulmonary function test abnormalities were higher in men than women. These gender differences may be due to differential expression of certain proteins in this group.